Correction: Corrigendum: Genome-wide association of polycystic ovary syndrome implicates alterations in gonadotropin secretion in European ancestry populations - M. Geoffrey Hayes (Nature Portfolio, 2016)
Nature Communications 6: Article number: 7502 (2015); Published: 18 August 2015; Updated: 12 February 2016 In the original version of this Article the genetic locus 8p23.1 was incorrectly referred to as 8p32.1 throughout. For example, in the Abstract, the sentence beginning ‘Three loci reach genome-wide significance in the case-control meta-analysis…' originally read ‘Three loci reach genome-wide significance in the case-control meta-analysis, two novel loci mapping to chr 8p32.